The Present of the Future. - Witzgall, Susanne; Stakemeier, Kerstin (Diaphanes, 2017)
"As the world teeters on the brink of crisis and potentially catastrophic change, outlooks for the future have come to be characterized by anxiety. The skepticism that meets utopian visions of the future has given rise to collective nostalgia for seemingly reliable ideas. But rather than stagnate in idealism, how can artists and scholars create the potential for real change? The result of a lecture series held at the cx centre for interdisciplinary studies at the Academy of Fine Arts, Munich, The Present of the Future explores our current relationship to the future and considers strategies for artists and scholars to establish effective action for shaping alternative futures. Contributors to the book approach this problem from the perspective of diverse disciplines, including art, design, architecture, and philosophy."--